Potensi dan Tingkat Pemanfaatan Sumberdaya Ikan Unggulan di Kabupaten Manggarai Barat - Edizul A Sadir; Chandra Nainggolan; Dedy H. Sutisna (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
The purpose of this study is to determine the potential superior commodities fisheries and calculate the potential and level of utilization. This research was conducted using survey methods and field observations. Data collection was carried out in two stages, namely primary data collection in the field with direct observation and secondary data using a questionnaire. Sources of data obtained based on information from respondents through interviews based on a list of questions or questionnaires. Analysis of the data used uses scoring with a value function as standardization of values, to determine the source of superior fish and surplus production with the Schaefer approach to calculate abundance and utilization rates. The results showed superior fish resources based on aspects of production value; market price; marketing area; and commodity value-added. grouper commodity is the top seed with a total value of 2,39. abundance or sustainable potential of grouper is 423 tons/year, optimum effort to utilize grouper is 3,470 hand line units, the amount of catch allowed is 339 tons/year, and the utilization rate reaches 70% (Fully Exploited) meaning that the capture effort is maintained with a strict monitor.